Berberine promotes peri‐implant osteogenesis in diabetic rats by ROS‐mediated IRS‐1 pathway. (24th November 2020) - Shao, Jingjing; Liu, Shibo; Zheng, Xiao; Chen, Jing; Li, Lei; Zhu, Zhimin
Abstract: Accompanying with diabetes mellitus‐induced osteoporosis (DM‐OS), diabetic patients show poor peri‐implant osteogenesis after implantation for dentition defect. Berberine (BBR), a candidate oral hypoglycemic agent, is a promising agent for treating DM‐OS. In this study, BBR was applied on DM rats and high‐glucose‐cultured bone mesenchymal stem cells (BMSCs) to investigate its therapeutic mechanism on DM‐OS, thus laying a theoretical basis for the future application of BBR in implant restoration. Phenotypes were assessed in the DM rats after 4 w of gavage with BBR. Furthermore, BMSCs were cultured with high glucose and BBR. Cell Counting Kit‐8, 2′, 7′‐dichlorofluorescin diacetate (H2 DCF‐DA), quantitative real‐time PCR (qRT‐PCR), and western blot were performed to estimate the cell proliferation, oxidative stress, and osteogenic differentiation. Moreover, the DM rats treated with BBR and insulin receptor substrate‐1 anti‐sense oligonucleotide (IRS‐1‐ASO) underwent a 4‐w implant‐healing period and then micro computed tomography (Micro‐CT) and histology were performed to verify the mechanism. Results showed that the 4‐w administration of BBR markedly improved the glucose metabolism and bone metabolism in the DM rats. in vitro experiments revealed that BBR alleviated high‐glucose‐inhibited osteogenesis of the BMSCs by upregulating reactive oxygen species (ROS)‐mediated IRS‐1 signaling. Besides, injection of IRS‐1‐ASO abolished the BBR promotion of implant osseointegration in the DM rats. In conclusion, targeting ROS‐mediated IRS‐1 signaling, BBR acted as an efficient agent to advance osseointegration in DM, which indicated that BBR use is a good strategy for future implants restoration in diabetic patients.